Fuel Price Subsidies in Gabon : Fiscal Cost and Distributional Impact - Leigh, Daniel (IMF Working Papers; Working Paper ;, 2006)
This paper looks at the fiscal cost and distributional impact of implicit fuel price subsidies in Gabon, where fuel prices have remained largely unchanged since 2002. Using estimated implicit import parity prices, we evaluate the total fiscal cost of the subsidies at 3.2 percent of non-oil GDP in 2005-more than total public health expenditures. We also analyze the distribution of the subsidies using household survey data and find that the bulk of the subsidies benefit higher-income households. Finally, we suggest use of a number of existing programs to provide a more targeted and cost-effective means of protecting the real incomes of lower-income households from the effects of energy price increases.